2009
DOI: 10.2202/1934-2659.1411
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Phase and Chemical Equilibrium on the Quaternary System Acetic Acid, n-Butanol, Water and n-Butylacetate

Abstract: The correlation of the data for phase and chemical equilibrium in acetic acid-n-butanol-water-n-butylacetate is presented. The azeotropic properties, the topological structure and the existence of a reactive azeotrope are discussed. The data are correlated by Hayden-O'Connell second virial coefficients and NRTL. Chemical equilibrium constant has a strong influence on the reactive azeotrope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Unfortunately a lack of data from different literature results at various temperatures as was shown in 17 does not allow us to determine the preferable value of K a . The only available literature data on the thermodynamic constant at the investigated temperature 318.15 K are presented in the paper.…”
Section: Calculation Of the Thermodynamic Equilibriummentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately a lack of data from different literature results at various temperatures as was shown in 17 does not allow us to determine the preferable value of K a . The only available literature data on the thermodynamic constant at the investigated temperature 318.15 K are presented in the paper.…”
Section: Calculation Of the Thermodynamic Equilibriummentioning
confidence: 99%
“…The authors noted that the experimental and calculated data are in sufficient agreement with each other, though all used thermodynamic models had problems with simulation of the equilibrium constant in regions with low content of one or more components. Campanella and Mandagaran , reported thermodynamic equilibrium constant K a of the system acetic acid– n -butyl alcohol– n -butyl acetate–water at 365.0–366.66 K determined with the use of the equation from paper from VLE and LLE data. In, the authors emphasize that the values of thermodynamic equilibrium constants in different temperature ranges vary from 10 to 60 for different authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERD process has several advantages and economic benefits, including reversing chemical equilibrium in favour of water removal, achieving required selectivity, and producing high purity products. The chemical equilibrium constant strongly influenced the azeotropic point (14). Kang et al suggested an area for the heterogeneous ERD process that is thermodynamically infeasible, as indicated by reaction and phase equilibrium constraints.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, in ref ., we paid attention to the articles devoted to chemical equilibrium (CE) in the mixture under study. Despite the importance of these studies for reactive distillation, there are only a few available studies on this topic in the literature, not to mention the critical phenomena in such systems. The compositions of the critical phases were studied mainly in our studies. ,, It should be noted that work deals with a special information about the critical point of LLE on the surface of CE.…”
Section: Introductionmentioning
confidence: 99%